Students learning about evolution through a comic book - Johanna Aringer; Lars Wallner; Ammie Berglund (Evolution: Education and Outreach)
Abstract Background Evolution is a fundamental concept in biology education, recently emphasized in the Swedish curriculum for Year 4–6. However, teaching evolution poses challenges, necessitating innovative educational tools. This study explores the development and use of a comic book, Cats on the Run–A Dizzying Evolutionary Journey, designed to teach evolutionary concepts to young students through a narrative involving two modern-day house cats traveling through time and space. Results To explore what function the material has for students’ meaning making we analyze what students describe to have learned working with the comic Cats on the Run, and how aspects of the comic book are reflected in the students’ self-reported learning. The study involved 159 students from Grades 4–6 who used the comic book in their biology lessons. Analysis of student survey responses revealed that the students draw on the comic’s narrative and imagery as they report on learning about key evolutionary concepts such as variation, natural selection, heredity, and evolutionary patterns. Analysis of student survey responses revealed that the comic facilitated meaning making about key evolutionary concepts such as variation, natural selection, heredity, and evolutionary patterns. Students were often referencing the comic's narrative and imagery as they reported their learning. Conclusions The findings suggest that the comic book is a valuable educational tool. More specifically, the narrative and multimodal aspects of the comic support meaning making and learning. This study highlights the importance of thoughtfully designed educational materials and suggests that combining different resources can enable discussion and learning of complex scientific concepts.